Tolerance of immersive head-mounted virtual reality among older nursing home residents - Rmadi, Hajer; Maillot, Pauline; Artico, Romain; Baudouin, Edouard; Hanneton, Sylvain; Dietrich, Gilles; Duron, Emmanuelle (Frontiers in Public Health, 2023)
Virtual Reality (VR) is a tool increasingly used in the ageing population. Head-Mounted Displays (HMD) are stereoscopic vision devices used for immersive VR. Cybersickness is sometimes reported after HMD VR exposure. Cybersickness severity and anxiety sate reflect VR low tolerance. We aimed to evaluate HMD VR tolerance among older nursing homes residents through cybersickness and anxiety state. Thirty-six participants were included in this preliminary study, 33 of whom (mean age: 89.33 ± 5.48) underwent three individual HMD VR sessions with 3 different contents. Cybersickness occurrence and severity were scored by the Simulator Sickness Questionnaire (SSQ) after each session. An anxiety state was assessed by the State Trait Anxiety Inventory form Y-A before and after each session. Anxiety trait (using State Trait Anxiety Inventory form Y-B) was also evaluated before and after the experiment. 92% (33/36) patients completed all 3 sessions of which 61% (20/33) did not report any cybersickness symptom (SSQ=0). Six participants reported significant cybersickness (defined by a SSQ score⩾10) in at least one session. Only 2 participants stopped the study after the first exposure because of cybersickness. Age, cognitive function, anxiety trait and well-being were not associated with cybersickness. Mean anxiety state decreased significantly from pre-to post-session. This immersive HMD VR experience was well tolerated among nursing homes dwellers. Further larger studies in this population to identify CS determinants are needed in order to use HMD VR on a standard basis.